The spread of covid-19 disease and the health of Nigeria - Abah*, R.T. (International Journal of Mathematical Analysis and Modelling, 2023)
COVID-19 is a major cause of death till date, claiming many lives in Nigeria and around the world. Nigeria was classified as one of the countries in Africa that had COVID-19 disease in 2020. February 27,2020, was when the first confirmed case of the novel coronavirus was reported in Nigeria. This was another terrible time when the health of Nigerians was under another serious attack apart from corruption and other economic challenges facing the country. In this study, Mathematical models are the major tools used for studying the transmission dynamics of covid-19. In this journal, we are considering a model on the spread of covid-19 disease and the health of Nigeria and analysed. the equilibrium states of the model which are the disease-free equilibrium states and the endemic equilibrium states were obtained and based on the Routh-Hurwitz criterion, the eigenvalues model equations have negative real parts, that is if and only if all the eigenvalues are negative, then the condition for stability is satisfied.